Health Survey in a Peruvian health system (ENSSA): design, methodology and general results - Renán Quispe Llanos; Rofilia Ramírez Ramírez; Martha Tizón Palacios; Claudio Flores Flores; Alfredo Borda-Olivas; Roger Araujo Castillo; Juan Guanira; Risof Solis Condor; Manuel Catacora Villasante; Yamilée Hurtado-Roca (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To report the design, methodology and initial results of the National Socioeconomic Survey of Access to Health of the EsSalud Insured. RESULTS There were interviews in 25,000 homes, surveying 79,874 people, of which 62,659 were affiliated to EsSalud. The insured people are mainly males (50.6%) with a higher technical education level (39.7%). The insured population has mostly independent (95.0%) and own (68.1%) home. Only 34.5% of the insured practice some sport or physical exercise; 14.0% of the population suffers from a chronic disease; 3.5% have diabetes; and 7.1%, arterial hypertension. In the last three months, 35.4% of the members needed medical attention; of these, only 73.1% received health care and the remaining 10.9% were treated in pharmacies or non-formal health care services. RESULTS The 25,000 homes were interviewed, surveying 79,874 people, of which 62,659 were affiliated to EsSalud. The insured people are mainly males (50.6%) with a higher technical education level (39.7%). The insured population has mostly independent (95.0%) and own (68.1%) home. Only 34.5% of the insured practice some sport or physical exercise; 14.0% of the population suffers from a chronic disease; 3.5% have diabetes; and 7.1%, arterial hypertension. In the last three months, 35.4% of the members needed medical attention; of these, only 73.1% received health care and the remaining 10.9% were treated in pharmacies or non-formal health care services. CONCLUSIONS This survey is the first performed in the population of EsSalud affiliates, applied at the national level, and has socio-economic and demographic data of the insured, their distribution, risk factors of health, prevalence of health problems and the degree of access to health services.